Mitigation of heat island effect by green stormwater infrastructure: a comparative study between two diverse green spaces in Nanjing - Xu, Haishun; Sheng, Kai; Gao, Jing (Frontiers in Ecology and Evolution, 2023)
Studies have shown that green spaces and water bodies can alleviate heat island effects. However, uncertainty remains regarding the characteristics and influence of Green Stormwater Infrastructures (GSIs) on the cooling effects under different weather conditions. To address this issue, a comparative study was conducted between the green spaces in a wetland park with GSIs and a general green space without GSIs. In this study, atmospheric temperatures were collected from both green spaces using mobile measurements to compare the cold island effect. In addition, the precise characteristics of the surface temperatures of the underlying surfaces in the wetland park were explored using an Unmanned Aerial Vehicle (UAV). The results revealed that green spaces with GSIs had a stronger cooling effect on the surrounding thermal environment than green spaces without GSIs, in most cases.The heat fluxes of different types of underlying surfaces in green spaces with different GSIs varied at different time periods. During the daytime, permeable pavement and some grasslands had a warming effect. The cooling effect of the other underlying surfaces was in the order of water bodies>arbors>shrubs>grasslands. At night, the changes in heat flux were lower, and only the arbors showed cooling due to evapotranspiration. These findings may provide innovative ideas and methods for planning GSIs to mitigate the urban heat island effects.